Directed Molecular Stacking for Engineered Fluorescent Three‐Dimensional Reduced Graphene Oxide and Coronene Frameworks. Issue 12 (4th December 2019) - Mao, Boyang; Cortezon‐Tamarit, Fernando; Ge, Haobo; Kuganathan, Navaratnarajah; Mirabello, Vincenzo; Palomares, Francisco J.; Kociok‐Köhn, Gabriele; Botchway, Stanley W.; Calatayud, David G.; Pascu, Sofia I.
Abstract: Three‐dimensional fluorescent graphene frameworks with controlled porous morphologies are of significant importance for practical applications reliant on controlled structural and electronic properties, such as organic electronics and photochemistry. Here we report a synthetically accessible approach concerning directed aromatic stacking interactions to give rise to new fluorogenic 3D frameworks with tuneable porosities achieved through molecular variations. The binding interactions between the graphene‐like domains present in the in situ‐ formed reduced graphene oxide (rGO) with functional porphyrin molecules lead to new hybrids via an unprecedented solvothermal reaction. Functional free‐base porphyrins featuring perfluorinated aryl groups or hexyl chains at their meso ‐ and β ‐positions were employed in turn to act as directing entities for the assembly of new graphene‐based and foam‐like frameworks and of their corresponding coronene‐based hybrids. Investigations in the dispersed phase and in thin‐film by XPS, SEM and FLIM shed light onto the nature of the aromatic stacking within functional rGO frameworks (denoted rGOFs) which was then modelled semi‐empirically and by DFT calculations. The pore sizes of the new emerging reduced graphene oxide hybrids are tuneable at the molecular level and mediated by the bonding forces with the functional porphyrins acting as the "molecular glue". Single crystal X‐ray crystallography described the stacking of a perfluorinated porphyrin with coronene, which can be employed as a molecular model for understanding the local aromatic stacking order and charge transfer interactions within these rGOFs for the first time. This opens up a new route to controllable 3D framework morphologies and pore size from the Ångstrom to the micrometre scale. Theoretical modelling showed that the porosity of these materials is mainly due to the controlled inter‐planar distance between the rGO, coronene or graphene sheets. The host‐guest chemistry involves the porphyrins acting as guests held through π‐π stacking, as demonstrated by XPS. The objective of this study is also to shed light into the fundamental localised electronic and energy transfer properties in these new molecularly engineered porous and fluorogenic architectures, aiming in turn to understand how functional porphyrins may exert stacking control over the notoriously disordered local structure present in porous reduced graphene oxide fragments. By tuning the porosity and the distance between the graphene sheets using aromatic stacking with porphyrins, it is also possible to tune the electronic structure of the final nanohybrid material, as indicated by FLIM experiments on thin films. Such nanohybrids with highly controlled pores dimensions and morphologies open the way to new design and assembly of storage devices and applications incorporating π‐conjugated molecules and materials and their π‐stacks may be relevant towards selective separation membranes, water purification and biosensing applications. Abstract : By introducing a panel of functional porphyrin molecules, new 3D hierarchical structures incorporating reduced graphene oxide can be achieved. The pore size of the framework can be finely tuned and reduced to a sub‐micron scale for the first time by careful selection of the porphyrin. Experimental and theoretical studies proposed that the pore size diminishing was due to strong local interactions between the designed porphyrin and rGO, mediated by donor‐acceptor interactions, which are maintained in the solution and in thin film.